Pencegahan Perilaku Bullying Melalui Internalisasi Nilai-Nilai Akhlak Islami di Madrasah Ibtidaiyah Negeri 1 Kota Bengkulu - Zinatul Hayati; Zulkarnain Syapal (UIN Fatmawati Sukarno Bengkulu, 2023)
The problem in this study is how to implement the strategy of internalizing Islamic moral values in preventing bullying behavior at Madrasah Ibtidaiyah Negeri 1 Bengkulu City. The problem that is the focus of this study uses a qualitative approach. Qualitative research is research that produces descriptive data in the form of written words. or word of mouth from people and observable behavior. The results showed that: First, the strategy of internalizing Islamic religious values in preventing bullying behavior at MI Negeri 1 Bengkulu City was carried out through academic and non-academic activities. The strategies used are exemplary strategies, habituation strategies, advice giving strategies and disciplinary strategies. Second, the prevention of bullying behavior at MI Negeri 1 Bengkulu City is to give punishments for bullying behavior. Such as punishment for memorizing selected letters, punishment for writing Yasin letters and punishment for school service. Third, the inhibiting factors from within the students themselves because of the different characters of students and from different backgrounds of students so that the coaching process carried out by teachers sometimes does not go well with students who can understand and do well the coaching and there are students who cannot carry out the coaching properly.